Superconducting Carbon‐Cage Network with Tc of 109 K at Ambient Pressure - Z. F. Ye; David J. Singh; Y. N. Huang; Guo‐Hua Zhong; Hai‐Qing Lin (Advanced Science)
Abstract A novel carbon‐cage network was reported, denoted as C18, found to be a low energy structure by first principles particle swarm structure search. The compound exhibits high temperature electron–phonon ambient pressure superconductivity with Tc = 79 K for elemental doping and can be raised to Tc = 109 K by appropriate hole doping. Analyses of the phonon spectra, molecular dynamics simulations, and enthalpy differences relative to analogous structures synthesized experimentally all suggest that the hole‐doped high‐Tc structure is a viable candidate for experimental synthesis.